1974
DOI: 10.1088/0031-9155/19/5/003
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum perturbation and energy deposition models for stopping power ratio calculations in general cavity theory

Abstract: A new theoretical model is introduced for the calculation of the absorbed dose in a cavity irradiated with X- or gamma -rays. It provides a method for evaluating the electron spectrum in the cavity by means of data on transmission, energy degradation and backscatter. Spencer's two-step model for energy deposition has been modified. The results are fitted to the Burlin expression. This yields a calculated value for the attenuation coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 16 publications
1
24
2
Order By: Relevance
“…These estimations are not so far from those resulting from the relations given by Burlin and Chan (1969) and by Janssens et al (1974), i.e. 9.3 cm 2 g −1 and 6.5 cm 2 g −1 respectively for graphite.…”
Section: Calculation Of Correction Factorscontrasting
confidence: 51%
See 2 more Smart Citations
“…These estimations are not so far from those resulting from the relations given by Burlin and Chan (1969) and by Janssens et al (1974), i.e. 9.3 cm 2 g −1 and 6.5 cm 2 g −1 respectively for graphite.…”
Section: Calculation Of Correction Factorscontrasting
confidence: 51%
“…According to the exponential decay and build-up assumption of electron fluence (Burlin 1966) or more exactly of energy deposition (Janssens et al 1974), one can write…”
Section: Calculation Of Correction Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (4.7) gives d with β given by e −βR CSDA = 0.04, using R CSDA for electrons of the incident photon energy. 125 Loevinger Equation (4.7) gives d with β (in cm −1 ) given by β = (16ρ cav )/(T max − 0.036) 1.4 where ρ cav is the density of the cavity in g/cm 3 and T max is the maximum kinetic energy of electrons in MeV, taken as the incident photon energy, which must be > 0.036 MeV. 126 weighted sum…”
Section: Burlin-janssensmentioning
confidence: 99%
“…where R max is an empirical range. Janssens et al 125 suggested using the extrapolated range for R. In this study, F is assumed to be unity so that R = R CSDA . The 'Burlin-Chan' method uses x = 0.01, as suggested by Burlin and…”
Section: Burlin-janssensmentioning
confidence: 99%